MASKULINITAS DAN FEMININITAS DALAM ANIME KIMI NO NA WA KAJIAN RESPON PEMIRSA - Fajria Noviana; Retno Wulandari (Diponegoro University, 2017)
Masculinity and femininity are never-ending subjects. This research aims at observing young generation’s perception on masculinity and femininity in Japanese animee Kimi no Na wa. In addition this research also brings input on how young generation reacts on masculinity and femininity. By using viewer’s response method, this research is conducted among 15 (fifteen) Japanese Department students and 15 (fifteen) Engish Department students of Universitas Diponegoro.The finding shows that young generation generally view that there is no significant differences between sex and gender role. Meanwhile, in the relation with the movie, responden assert their agreement on the description of masculinity and femininity through the male and female characters, although generally respondents from English Department prefer East masculinity and West femininity. This view can be used as the basic how older people build relation with young people due to differences in age and point of view.